Chronic fatigue syndrome and epigenetics: The case for hyperbaric oxygen therapy in biomarker identification - Shah, Rajit J (Journal of Pulmonology and Respiratory Research, 2021)
Chronic fatigue syndrome (CFS) is a poorly-understood respiratory condition that affects millions of individuals. Hyperbaric oxygen therapy (HBOT) is a treatment option being considered to address CFS as it is suggested to combat fatigue and increase oxygenation. HBOT provides two opportunities in advancing research of CFS: it may provide data on symptom amelioration and be utilized in the search for a biomarker. By either identifying biomarkers before using HBOT to compare epigenomes of patients before and after treatment or using HBOT to find epigenetic discrepancies between patients with and without treatment, matching epigenetic regulation with symptom amelioration may significantly advance the understanding of the etiology and treatment mechanism for CFS. EPAS1/HIF-2α is a leading candidate for an epigenetic biomarker as it responds differentially to hypoxic and normoxic conditions, which degrades more slowly in hypoxic conditions. Epigenetic regulation of EPAS1/HIF-2α in such differential conditions may be explored in HBOT experiments. In addition to HBOT as a promising treatment option for CFS symptoms, it may aid the identification of biomarkers in CFS. Further research into both outcomes is strongly encouraged.